Evaluation of the Antioxidative Properties of N-Acylamino-Substituted Tricyclic Imides - Gul, Melek; Kulu, Irem; Peksel, Aysegul; Ocal, Nuket (HINDAWI LTD, 2013)
New N-acylamino-substituted tricyclic imides have been screened for scavenging ability against the free radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH center dot), chelating activity on ferrous ions, and reductive potential. The results were compared with synthetic antioxidants BHT, BHA, and Trolox. The compounds exhibited different levels of antioxidant activity in all tests.
Keywords: DOMINO-HECK REACTIONS; CYCLIC IMIDES; UNSATURATED DICARBOXIMIDES; ANXIOLYTIC ACTIVITY; ANALOGS; EPIBOXIDINE; HYDROARYLATION; TANDOSPIRONE; EPIBATIDINE; DERIVATIVES; Chemistry